Effects of prostaglandin E2 on cells cultured from the rat organum vasculosum laminae terminalis and median preoptic nucleus. (28th January 2016) - Simm, B.; Ott, D.; Pollatzek, E.; Murgott, J.; Gerstberger, R.; Rummel, C.; Roth, J.
Highlights: PGE2 evokes Ca 2+ -signals in cells cultured from the rat OVLT. PGE2 modulates the strength of glutamate-evoked Ca 2+ signals in cells cultured from the rat MnPO. These MnPO-derived cells include a population of GABAergic neurons. PGE2 reduces LPS-induced release of TNF-α from OVLT and MnPO rat primary cultures. Abstract: The time course of the induction of enzymes responsible for the formation of prostaglandin E2 (PGE2 ) after an inflammatory insult, in relation to the concomitant febrile response, suggests that peripherally generated PGE2 is involved in the induction of the early phase of fever, while centrally produced PGE2 exerts pyrogenic capacities during the later stages of fever within the hypothalamic median preoptic nucleus (MnPO). The actions of peripherally derived PGE2 on the brain might occur at the level of the organum vasculosum laminae terminalis (OVLT), which lacks a tight blood–brain barrier and is implicated in fever, while the effects of PGE2 within the MnPO might interfere with glutamatergic neurotransmission within a recently characterized central efferent pathway for the activation of cold-defence reactions. Using the fura-2 ratio imaging technique we, therefore, measured changes of the intracellular Ca 2+ -concentration in primary neuroglial microcultures of rat OVLT and MnPO stimulated with PGE2 and/or glutamate. In cultures from the OVLT, as opposed to those derived from the MnPO, substantial numbers of neurons (8% of 385), astrocytes (19% of 645) and microglial cells (28% of 43) directly responded to PGE2 with a transient increase of intracellular Ca 2+ . The most pronounced effect of PGE2 on cells from MnPO microcultures was its modulatory influence on the strength of glutamate-induced Ca 2+ -signals. In 72 out of 512 neurons and in 105 out of 715 astrocytes PGE2 significantly augmented glutamate-induced Ca 2+ -signals. About 30% of these neurons were GABAergic. These observations are in agreement with putative roles of peripheral PGE2 as a directly acting circulating agent at the level of the OVLT, and of central MnPO-intrinsic PGE2 as an enhancer of glutamatergic neurotransmission, which causes disinhibition of thermogenic heat production, a crucial component for the manifestation of fever. In microcultures from both brain sites investigated incubation with PGE2 significantly reduced the lipopolysaccharide-induced release of cytokines (tumor necrosis factor-α and interleukin-6) into the supernatant. PGE2, thus, seems to be involved in a negative feed-back loop to limit the strength of the brain inflammatory process and to play a dual role with pro- as well as anti-inflammatory properties.